Biotic homogenization in multisystem cascade reservoirs: insights from sedimentary photopigment analysis - Cardoso-Silva, Sheila [UNESP]; Trevizani, Tailisi Hoppe; Figueira, Rubens Cesar Lopes; Pompêo, Marcelo [UNESP]; Krammer, Olga; Picazo, Antonio; Vicente, Eduardo; Moschini-Carlos, Viviane [UNESP] (Springer Nature, 2024)
The existing literature provides limited insights into the dynamics of phytoplankton communities and the spatial heterogeneity of physicochemical parameters in multisystem cascade reservoirs (interconnected reservoirs derived from different rivers). The existing studies are concentrated on cascade reservoirs (interconnected reservoirs derived from the same river). To address this knowledge gap, the aims of the present study were as follows: (1) investigate the spatial heterogeneity, within and between reservoirs, of geochemical parameters associated with the eutrophication process, considering total phosphorus, chlorophyll-a, pheophytin, and metals (chromium, copper, nickel, lead, zinc, iron, and manganese); (2) evaluate sediment quality at the designated locations; (3) assess differences in the richness and concentration of sedimentary photopigments between the reservoirs. Application of principal component analysis revealed discernible gradients for the abiotic variables, although the differences were not statistically significant (one-way PERMANOVA test, p > 0.05). The observations suggested a tendency towards spatial homogeneity within and between the reservoirs. The metal concentrations were consistent with regional reference values, while phosphorus levels in the sediment approached the threshold for classification as pollution (~ 2000 mg/kg). Analysis of pigments indicated low dissimilarity among the reservoirs, which could be mainly attributed to the eutrophication process and high connectivity of the sampled areas. To counteract ongoing biotic homogenization, it is essential to reduce nutrient inputs and invest in ecological protection and restoration programs. The analysis of sedimentary photopigments provides an efficient and cost-effective alternative way to assess phytoplankton communities.
Keywords: Biotic homogenization; Connectivity; Eutrophication; Heterogeneity; Metals; Phosphorus